Aksjologia stanów nadzwyczajnych w Polsce - Powałowski, Andrzej (PRAWO i WIĘŹ, 2025)
The issue of states of emergency should be viewed in the context of the goal of protecting the most valuable assets of the state and its citizens (such as security, public order, and the constitutional system) in the face of specific threats. By its very nature, it requires the restriction, and sometimes suspension, of human freedoms and rights, as well as those of economic operators. Therefore, this is an area of ​​inquiry fraught with intense conflicts of values ​​– on the one hand, the overarching common goods, and on the other, fundamental human rights and the freedom to pursue economic activity. A state of emergency is a legal regime that allows state bodies to exercise public authority in a specific manner. These bodies are responsible for assessing the justification for declaring a specific state of emergency, and the undeniable criteria that should guide them include sets of values ​​related to states of emergency, which have specific sources and are in various configurations.